Optimizing Vermicelli Production: Flour Evaluation Using WASPAM Methodology for Informed Decision-Making in the Food Industry - Immanuela, Noviany (International Enterprise Integration Association, 2024)
This research employs the Weighted Aggregated Sum Product Assessment Method (WASPAM) to evaluate and determine the most suitable flour for vermicelli production. The study aims to streamline the complex decision-making process inherent in flour selection by considering crucial criteria texture, gluten content, and protein levels to assess multiple flour options comprehensively. The assessment highlights texture as a pivotal criterion significantly influencing the suitability of flour for vermicelli production. Flour samples excelling in texture consistently ranked higher, emphasizing its paramount importance in achieving desired consistency and mouthfeel in vermicelli noodles. Additionally, while gluten content and protein levels played substantial roles, a balanced performance across criteria often resulted in competitive suitability scores, emphasizing the necessity of a holistic approach in flour selection. The findings offer valuable insights for stakeholders in the food industry, providing guidance for optimal flour selection strategies aligned with quality preferences and market demands. The research recommends a refined approach to weight allocation, particularly considering the pronounced influence of texture.